Can intraoperative ultrasound visualize the closed reduction and elastic intramedullary nail fixation processes of double forearm fractures in children?. Issue 12 (26th March 2021) - Yang, Xiaodong; Li, Lang; Tang, Xueyang; Xiang, Bo; Wen, Tianfu
Abstract : Abstract: To evaluate the feasibility of utilizing ultrasonography to monitor the fracture reduction and elastic intramedullary nail fixation processes in treating children with double forearm fractures. A retrospective analysis of 30 children with double forearm fractures treated at our hospital between January 2016 and July 2018. The children were aged 3 to 10 years. All patients were treated with closed reduction and internal fixation with elastic intramedullary nails using intraoperative ultrasound monitoring and intermittent radiographic imaging. The closed reduction and fixation were successful in all patients. The operation times ranged from 16 to 30 minutes, averaging 21 minutes. No neurovascular injuries occurred during closed reduction and nail insertion. Moreover, closed reduction was successful in the first attempt in 86.7% of patients. All patient outcomes were optimal, lacking serious complications during follow-ups. Intraoperative ultrasound monitoring can clearly show the shape and changes in fracture ends, distal growth plates, and surrounding soft tissues, and fracture reduction and passage of elastic nail processes at fracture ends during closed reduction; therefore, visualizing closed reductions can be achieved. The combination of intraoperative ultrasound and radiographic imaging can ensure operative effects and significantly reduce radiation exposure for both doctors and patients. An adequately powered prospective randomized trial is required to confirm our findings.